Not in vain ; 14th what God hath wrought amongst the Kanakas in Queensland being Report of the Queensland Kanaka Mission for the year 1899-1900 (1900)
Contents includes : Queensland Kanaka Mission : Object and principles (revised).
Photocopy.
Keywords: Queensland Kanaka Mission; Brethren movement -- missions -- Australia -- history